The Mediator CSR Plays the Effective Leadership Belief Role for Resource Dilemma Handling Leadership in Organizational Commitment During Sustainability Development - Chan, Kuo-Hua; Lin, Shang-Ping; Shih, I-Tung (Frontiers in Psychology, 2022)
The authors aim to explore a better fitting leadership style that is designed for the sustainable era in believing and committing to work for cherishing resources and developing the organization towards a new sustainable direction. This study developed the questionnaire items of the Resource-Dilemma-Handling-Leadership (RDHL) scale, representing a new sustainable era's new leadership style, and then to compare it with the transformational leadership style in order to highlight the importance of RHDL for sustainable development. This study took companies, which have more than 100 employees in Taiwan as research samples. Those companies were selected because they were socially tagged as being operating continuously for more than 20 years and identifying themselves with the operational orientation of social responsibility as their business philosophy and core values for management. A total of 532 valid questionnaires were collected, with a 90.6% valid return rate, and tested with the SEM method. Consistent with the authors' inferences from the literature, the test results suggest that CSR plays the role of full mediator between RDHL and OC. CSR itself is like a sense of responsibility, giving employees a sense of mission, to complete meaningful sustainability-relevant tasks in the organization. RDHL, compared with TL, has a better prediction power on CSR and OC. Theoretically, this study implies that the impact of leadership of the organization on OC in the aspects of sustainable development should be going through the influence of the ELB system in the form of CSR to promote the organization's internal and external organizational CSR performance, with added internal strengthening power from OC. Practically, the new RDHL concepts brought up by this study include the training and enhancement of leadership skills based on the content of the scale items being explored. The new RDHL scale contains a comprehensive description of the spirit of the new sustainable era's leadership style. Also, the future applications of RDHL ideas in the form of human resource development should help the realization of the ideally sustainability behavioral patterns of leaders and employees in the organizations.